THE ADSORPTION OF GOLD TO GALENA SURFACES: CALCULATION OF ADSORPTION/REDUCTION ENERGIES, REACTION MECHANISMS, XPS SPECTRA, AND STM IMAGES - Becker U.; Hochella M.F.; Vaughan D.J. (My University, 1997)
In order to evaluate the thermodynamics and reaction mechanisms of the adsorption and reduction of gold on galena surfaces, reaction energies were calculated for the adsorption of AuCl-4 from solution and for the stepwise reduction of gold from Au(III) to Au(0) by using an ab initio cluster approach. The adsorption of gold chloride onto galena and the reduction from Au(III) to Au(0) were found to be slightly exothermic, but only if hydration energies are included. All adsorbate structures with intermediate oxidation states occupy local energy minima, that is, they are potentially metastable. Even though gold is in the formal oxidation state Au(III) in galena-AuCl3, the main electron transfer from the galena surface to the gold atom has already taken place by withdrawing about 0.1 unit charges from all sulfur atoms in the cluster. This mechanism explains the unique affinity of gold to semiconducting sulfide surfaces. Au(0) is stabilized by the formation of gold dimers and islands due to the formation of gold-gold metal bonds.The formation of gold islands is enhanced by the low activation energy for Au(0) diffusion along the S-S diagonal. We calculated this activation energy for diffusion to be less than four times the thermal energy if Au(0) travels along the S-S path by being in contact with the delocalized S 3p valence band density. Therefore, almost one percent of all Au(0) atoms can hop from one sulfur atom to the next at any time.A reaction path involving six-membered polysulfide rings was found to be much more exothermic than reduction of gold chloride by galena alone. However, at the initial stage of gold reduction, reaction rates and the importance of a reaction path involving polysulfides may be limited by the availability of Pb-polysulfide or elemental sulfur.XPS spectra were calculated for the adsorbed gold, Au chlorides, and Au polysulfides. All these species cause similar peak chemical shifts of the S (2p32) and S(2s) XPS peaks. Therefore, it is likely that experimentally obtained and fitted XPS peaks contain varying contribution of different oxidation states and gold ligands. Calculated XPS spectra also show how the charge density distribution of adsorbate structures influences the electronic structure of the underlying substrate.STS spectra were calculated in order to develop a tool that can help to identify which adsorbate structure is present at the surface and to study the local electronic structure of such sites. The most significant difference is the change of the local band gap which decreases from #1 eV for galena-Au(III)Cl3 and about 0.5 eV for galena-Au(I)Cl to a metal-like local environment with no bandgap for elemental gold in galena-Au and galena-Au2 (the bulk bandgap of fresh galena is #0.4 eV). The calculated STS spectrum of galena-Au2 was found to be very similar to STS spectra near the rim of the gold island.